Adaptable antigen matrix platforms for peptide vaccination strategies and T cell-mediated anti-tumor immunity. (December 2020) - Schetters, Sjoerd T.T.; Li, R.J. Eveline; Kruijssen, Laura J.W.; Engels, Steef; Ambrosini, Martino; Garcia-Vallejo, Juan J.; Kalay, Hakan; Unger, Wendy W.J.; van Kooyk, Yvette
Abstract: Injection of antigenic peptides has been widely used as a vaccine strategy to boost T cell immunity. However, the poor immunogenicity of single peptides can potentially be strengthened through modification of the tertiary structure and the selection of the accompanying adjuvant. Here, we generated antigenic peptides into non-linear trimers by solid phase peptide synthesis, thereby enhancing antigen presentation by dendritic cells to CD8 + T cells in vitro and in vivo . CD8 + T cells from mice vaccinated with trimers showed an KLRG1 + effector phenotype and were able to recognize and kill antigen-expressing tumor cells ex vivo . Importantly, trimers outperformed synthetic long peptide in terms of T cell response even when equal number of epitopes were used for immunization. To improve the synthesis of trimers containing difficult peptide sequences, we developed a novel small molecule that functions as conjugation platform for synthetic long peptides. This platform, termed Antigen MAtriX (AMAX) improved yield, purity and solubility of trimers over conventional solid phase synthesis strategies. AMAX outperformed synthetic long peptides in terms of both CD8 + and CD4 + T cell responses and allowed functionalization with DC-SIGN-binding carbohydrates for in vivo dendritic cell targeting strategies, boosting T cell responses even further. Moreover, we show that agonistic CD40 antibody combined with MF59 (AddaVax) emulsion synergistically improves the antigen-specific T cell response of the AMAX in vivo . Also, tumor-associated antigens and neo-antigens could be incorporated in AMAX for tumor-specific CD8 + T cell responses. Importantly, immunization with a mix of neoantigen AMAX could reduce tumor growth in a pre-clinical syngeneic mouse model. Hence, we provide pre-clinical support for the induction of effector CD8 + T cells through the adaptable AMAX platform as easy implementable peptidic vaccination strategy against any antigen of choice, including neoantigens for anti-tumor immunity. Graphical abstract: Image 1